2008
DOI: 10.1093/heapro/dam039
|View full text |Cite
|
Sign up to set email alerts
|

Relations between Internet use, socio-economic status (SES), social support and subjective health

Abstract: This study aimed to explore relations between Internet use, socio-economic status (SES), social support and subjective health. Participants were from representative samples between 15 and 80 years of age from seven different European countries. Two different survey datasets were used: (i) eHealth trends (eHT; N = 7934) and (ii) the European social survey (ESS2; N = 11248). Internet users who had used the Internet for health purposes were compared with Internet users who had not used it for health purposes. Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
106
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(121 citation statements)
references
References 23 publications
11
106
2
2
Order By: Relevance
“…At this point, a conclusion that seems more soundly supported by the data reported here, and elsewhere (Kelley & Gruber, 2010;Niemz et al, 2005;Wangberg et al, 2007), is that any relationship between the Internet and physical health occurs only when Internet usage is problematic for the individual, that is, becomes obsessive, results in neglecting self or social ties, or results in loss of control over one's online usage patterns. In other words, mere use of the Internet, per se, even if the daily time spent online is relatively high, is not itself strongly related to any physical health concerns individuals may experience.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…At this point, a conclusion that seems more soundly supported by the data reported here, and elsewhere (Kelley & Gruber, 2010;Niemz et al, 2005;Wangberg et al, 2007), is that any relationship between the Internet and physical health occurs only when Internet usage is problematic for the individual, that is, becomes obsessive, results in neglecting self or social ties, or results in loss of control over one's online usage patterns. In other words, mere use of the Internet, per se, even if the daily time spent online is relatively high, is not itself strongly related to any physical health concerns individuals may experience.…”
Section: Discussionsupporting
confidence: 72%
“…Demetrovics et al (2008) however, did report that, overall, while time spent online is not a factor, time spent online for non-work purposes is a relevant predictor of problematic Internet use. Wangberg et al (2007) utilizing a large sample from seven European countries reported some limited information regarding Internet use and a simple, one-question assessment of health ("How is your health in general?") indicating that Internet users reported slightly higher health scores compared to non-Internet users.…”
Section: Introductionmentioning
confidence: 99%
“…This test consists of different stages: (i) the action theory tests (27) which estimate the association between the SES indicators and the potential mediators (the different correlates of PA), resulting in a coefficients; (ii) the conceptual theory tests (27) which estimate the association between the potential mediators and the PA outcome, resulting in b coefficients for the mediators; (iii) the calculation of the product of the two coefficients (ab), representing the mediating effect; and (iv) the calculation of dividing ab by its standard error to assess the statistical significance of the mediating role. For the calculation of the standard error, the Sobel test (22,28) was used: SE ab 5 O(a 2 SE b 2 1b 2 SE a 2 ). The obtained value of ab/SE ab was then compared to a standard normal distribution (27) .…”
Section: Discussionmentioning
confidence: 99%
“…Current literature on social support shows how SNSs are likely to provide online social support (Ballantine & Stephenson, 2011;Crocker & Canevello, 2008;Hwang et al, 2010;Obst & Stafurik, 2010;Teoh, Chia, & Mohanraj, 2009;Wangberg et al, 2008;Wellman et al, 1996). Therefore, online social support is likely to be more productive through social involvement and improved online communication than offline social support (Kraut et al, 2002).…”
Section: Social Supportmentioning
confidence: 99%